Acceptable walking and cycling distances and functional disability and mortality in older Japanese adults: An 8-year follow-up study. (January 2023) - Tsunoda, Kenji; Nagata, Koki; Jindo, Takashi; Fujii, Yuya; Soma, Yuki; Kitano, Naruki; Okura, Tomohiro
Abstract: We prospectively investigated the association between acceptable travel distances (i.e., walking and cycling) and the incidence of functional disability and mortality among older Japanese adults. A baseline survey was conducted in 2013 among 7618 individuals aged ≥65 years in Kasama City, Japan, and they were tracked through the city's database until 2021. Acceptable travel distances were assessed using a questionnaire. Outcomes (i.e., functional disability and mortality) were gathered as binary (incident or not) with survival time. A multivariable-adjusted Cox proportional-hazards model indicated that shorter acceptable walking and cycling distances were markedly linked with higher risks of functional disability and mortality. In conclusion, acceptable distances of ≤500 m for walking and ≤1 km for cycling were associated with higher risks of functional disability and mortality among older adults. Highlights: This was an 8-year follow-up study based on an inventory survey in Kasama City. Data on functional disability and mortality were followed via the City's database. An acceptable walking distance of ≤500 m elevated the risk of both events. An acceptable cycling distance of ≤1 km was also linked with both events.